First-principles insights into Sn/Sc/Ag/Ni-doped Al2Cu structural, electronic, mechanical, and thermodynamic properties - Yuhua Jin; Sijun Yang; Xuefeng Lu; Yu Ni; xiao Li (Journal of Materials Research and Technology)
The addition of a third element to Al2Cu, the strengthening phase in copper-aluminum composites can modify its properties and consequently influence its strengthening effectiveness. In this study, first-principles calculations are employed to establish models of Al2Cu and its doped variants (Sn, Sc, Ni, Ag doping) for systematic examination of structural stability, electronic characteristics, mechanical performance, and thermodynamic behavior in these modified systems. The results show that the incorporation of doping elements such as Sn, Ni, and Ag can enhance the stability of the Al2Cu crystal, with the most significant effect observed for Ni doping in these elements, due to the strong covalent bonds formed from the hybridization of the d-orbitals of Ni and Cu. Additionally, the bulk modulus (104.15 GPa for the Sn–Al system), shear modulus (56.38 GPa for the Sn–Al system), and Young's modulus (143.29 GPa for the Sn–Al system) of Al2Cu are increased after doping different elements, and all doping systems show improved ductility. Phonon spectrum analysis indicates that the doped crystals with Sn, Ni, and Ag exhibit excellent dynamic stability, while the presence of imaginary frequencies after Sc doped leads to insufficient stability. The Debye temperature of the Ni-doped system is the highest (393 K), and the Helmholtz free energy is optimal at high temperatures, indicating that Ni doping effectively suppresses lattice distortions and vacancy defects caused by atomic thermal vibrations. This study elucidates that (Ni, Sn, Ag) doping enhances Al2Cu performance through electronic-phonon-thermodynamic multiscale synergistic mechanisms, establishing quantitative relationships between elemental doping and properties. It proposes integrated electronic-mechanical-thermodynamic criteria for element selection under high-temperature service conditions, while validating critical alloy design parameters via Sc-doped instability cases, providing theoretical guidance for developing heat-resistant copper-aluminum composites.